PERAN ORANG TUA DALAM MENUMBUHKAN KECERDASAN ANAK USIA DINI PERSFEKTIF SURAT AN-NAHL - Yulia, Ayu; Fadhila, Fadhila (LPPM Universitas Bina Bangsa, 2025)
The purpose of this study was to determine the role of parents in fostering the intelligence of early childhood based on the perspective of Surat An-Nahl. The early childhood development phase that lasts from the age of 0 to 6 years, which is considered a critical period in the formation of the basics of intelligence, character, and behavior. During this age range, children have high learning potential and curiosity. This study identifies the role of parents, namely providing appropriate stimulation, being a good role model, and ensuring balanced nutrition. In addition, parents are expected to support the moral and spiritual development of children by instilling positive values and gratitude. Through this approach, it emphasizes the importance of the role of parents in children's education, so that children are not only academically intelligent, but also have good character. The role of parents in creating a generation that is not only intellectually intelligent, but also has high moral and spiritual integrity, in accordance with the values contained in Surat An-Nahl.